The Role of Coworkers in Improving Employee Performance at the Padepokan Buffet Restaurant - Tahol, Triana Olivia; Farid Al Farizi; Ahmad Muafi; Iriani Ismail (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of writing this article is to discuss the role of colleagues in improving employee performance at the Padepokan Buffet Restaurant. This research uses a qualitative research method approach using two data sources, namely primary data through interviews and secondary data using literature studies. The analysis technique used in this research is descriptive analysis technique. The results of this study indicate that the role of coworkers has a significant impact on employee performance in restaurants. The effective role of coworkers can influence employee performance through several mechanisms. Through good teamwork, colleagues can increase employee productivity and work quality. Synergistic teamwork enables the exchange of knowledge and experience that can improve individual skills